Excess nitrogen responsive HvMADS27 transcription factor controls barley root architecture by regulating abscisic acid level - Smoczynska, Aleksandra; Pacak, Andrzej; Grabowska, Aleksandra; Bielewicz, Dawid; Zadworny, Marcin; Singh, Kashmir; Dolata, Jakub; Bajczyk, Mateusz; Nuc, Przemyslaw; Kesy, Jacek; Wozniak, Magdalena; Ratajczak, Izabela; et al. (Frontiers in Plant Science, 2022)
Nitrogen (N) is an important element for plant growth and development. Although several studies have examined plants’ response to N deficiency, studies on plants’ response to excess N, which is common in fertilizer-based agrosystems, are limited. Therefore, the aim of this study was to examine the response of barley to excess N conditions, specifically the root response. Additionally, genomic mechanism of excess N response in barley was elucidated using transcriptomic technologies. The results of the study showed that barley MADS27 transcription factor was mainly expressed in the roots and its gene contained N-responsive cis-regulatory elements in the promoter region. Additionally, there was a significant decrease in HvMADS27 expression under excess N condition; however, its expression was not significantly affected under low N condition. Phenotypic analysis of the root system of HvMADS27 knockdown and overexpressing barley plants revealed that HvMADS27 regulates barley root architecture under excess N stress. Further analysis of wild-type (WT) and transgenic barley plants (hvmads27 kd and hvmads27 c-Myc OE) revealed that HvMADS27 regulates the expression of HvBG1 β-glucosidase, which in turn regulates abscisic acid (ABA) level in roots. Overall, the findings of this study showed that HvMADS27 expression is downregulated in barley roots under excess N stress, which induces HvBG1 expression, leading to the release of ABA from ABA-glucose conjugate, and consequent shortening of the roots.